2021
DOI: 10.1186/s13063-021-05389-0
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal intervention for the treatment of veterans with COVID-19 requiring hospitalization (HITCH): a multicenter, phase 2 randomized controlled trial of best supportive care vs best supportive care plus degarelix: study protocol for a randomized controlled trial

Abstract: Background Therapeutic targeting of host-cell factors required for SARS-CoV-2 entry is an alternative strategy to ameliorate COVID-19 severity. SARS-CoV-2 entry into lung epithelium requires the TMPRSS2 cell surface protease. Pre-clinical and correlative data in humans suggest that anti-androgenic therapies can reduce the expression of TMPRSS2 on lung epithelium. Accordingly, we hypothesize that therapeutic targeting of androgen receptor signaling via degarelix, a luteinizing hormone-releasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The HITCH Trial was a multicenter, phase II, randomized clinical trial of standard care plus degarelix compared with standard care plus placebo to improve the clinical outcomes of male veterans who had been hospitalized owing to COVID-19. 14 The trial was conducted at 14 VA medical centers and funded by the VA Office of Research and Development. Patients were enrolled from July 22, 2020, to April 8, 2021.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The HITCH Trial was a multicenter, phase II, randomized clinical trial of standard care plus degarelix compared with standard care plus placebo to improve the clinical outcomes of male veterans who had been hospitalized owing to COVID-19. 14 The trial was conducted at 14 VA medical centers and funded by the VA Office of Research and Development. Patients were enrolled from July 22, 2020, to April 8, 2021.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion and exclusion criteria were reported previously, 14 and updated in eTable 1 in Supplement 2 . In brief, the trial enrolled men, aged 18 years and older who had a disease severity from COVID-19 that warranted hospitalization for supportive care but not invasive mechanical ventilation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Degarelix is a prescription medicine used in the treatment of advanced prostate cancer that works as a luteinizing hormone-releasing hormone (LHRH) antagonist, thus leading to lowered testosterone levels in the body. As a result, the Hormonal Intervention for the Treatment in Veterans With COVID-19 Requiring Hospitalization (HITCH) (NCT04397718) was initiated to test this hypothesis (Nickols et al, 2021). Although the HITCH trial reported that androgen suppression through Degarelix treatment did not improve outcomes in a small cohort of men hospitalized with COVID-19, other trials found proxalutamide, an androgen receptor antagonist, was an effective treatment for non-hospitalized patients with COVID-19 (Cadegiani et al, 2021;McCoy et al, 2021;Nickols et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…We are currently in the process of submitting IRBs for open-label clinical trials for other cases. Lastly, two mediKanren identified therapeutics have been tested in clinical trials: Degarelix for COVID-19 (NCT04397718) and ketamine for ADNP syndrome (NCT04388774) (Nickols et al, 2021).…”
Section: Figurementioning
confidence: 99%